Technological innovation as a factor of sustainable economic development of the region - T. A. Voronova,; A. P. Garnov; E. V. Loginova; S. Yu. Ayvazov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article explains the necessity and important role of innovation in industry and shows their impact on economy. There are indicators characterizing the position of Russian highly technological products on global market. Causes of low competitiveness of Russian producers were revealed. The article demonstrates the importance of new technologies for attaining sustainable development of industrial enterprises and analyzes indicators of innovation activity, which discloses the uneven development of the innovation system in different regions of the country. The authors ground the necessity of Russian industry passing over to a new level of development and identify the key lines in shaping the innovative infrastructure of regions. They underline specific features of pursuing innovation policy in Russia, highlight principle problems hindering the development of innovation processes and propose ways of their overcoming. A set of measures was designed aimed at smoothing out the lag of private sector development from the state one and at stimulating research and developments in the private sector. Research findings can be used to correct regional strategies of innovation development.